Analysis and Trends for the IT Market - de Sousa, Hiago Henrique; Lima, Victor Hugo Nascimento; Ribeiro, Moisés José Moreira; Resende, Otávio Henrique Lopes; Soares, Liziane Santos (Anais do Workshop de Sistemas de Informação (WSIS), 2024)
This paper explores the dynamic landscape of the Information Technology (IT) market, emphasizing key emerging sectors such as the Internet of Things (IoT), cloud computing, artificial intelligence (AI), and the gaming industry. It examines the significant growth and impact these areas have on the industry and professionals, particularly in the context of Brazil. The study highlights the challenges faced by IT professionals, including the need for continuous learning and adaptation to evolving tools and languages. Moreover, the paper discusses the ongoing effects of COVID-19 on the IT market, emphasizing the acceleration of digital transformation and the increasing demand for specialized talent. Data from industry surveys are analyzed to provide insights into the trends shaping the future of IT, both globally and within Brazil, where the shortage of qualified professionals remains a critical issue.